Digital Nomadism: Trends of European Labor Migration in Low-Cost Countries - Akbar Fasya Habibilla; Adhi Cahya Fahadayna (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2023)
Work activities are becoming increasingly mobile as a result of advancements in information technology. European productivity is changing to more flexible work approaches with internet processes. Many productive-age citizens from European countries with high living costs engage in digital nomadism activities. This research aims to explore the pull and push factors of the digital nomadism process and determine the motives for digital nomadism activities carried out by Europeans. Using netnography analysis tools and qualitative approaches, researchers are attempting to determine what factors influence and how European workers carry out digital nomadic activity patterns in Madeira, Portugal. As a result, researchers bring forth the descriptive outcomes of the analysis. In this article, researchers conclude that digital nomadism is a practice or, more accurately, a new way of life mostly practiced by remote workers with flexible work schedules. The idea of work-life balance is equally important to digital nomads. The growth of digital platforms that increasingly enable work to be done online drives the development of digital nomadism activities. This article will also go into greater detail on several pulls and push elements, as well as numerous issues about activities for digital nomads.